Estrangement, Nature and ‘the Flesh’ - Hailwood, Simon (Ethical theory and moral practice, 2014)
In this paper I address the question of what it is to be alienated from nature. The focus is alienation in the sense of estrangement, a ‘being cut off from’ a wider world. That we are so estranged is a claim associated with ecological critique of contemporary society. But what is it to be estranged from nature given that everything we are, do and produce, always remains within a wider nature? I explore the possibility that this might be understood with reference to Merleau-Ponty’s notion of ‘flesh’. I set the scene for this with some discussion of Honneth’s recent account of reification as a ‘distorted praxis’ and then, drawing upon Merleau-Ponty’s phenomenology of perception and especially his later ontology of flesh, develop the idea of estrangement from the natural world as an inadequate participation in a ‘primordial’ perceptual relation. This idea of estrangement brings together various elements of ecological critique. However, I argue that although this idea of estrangement might inform and help to articulate such a critique, it cannot be the sole concern of an environmental political philosophy: other kinds of alienation within the humanised environmental context need to be considered too.